Adaptation of Minahasa Local Wisdom (Maleo-Leosan) as Sociology Teaching Material - Siti Fathimah; Awaluddin Hasrin; Sangputri Sidik (STAI Hubbulwathan Duri, 2023)
This research aims to develop sociology teaching materials in Senior High Schools about the basic competence of recognising and identifying the realities of individuals, groups, and social relations in society. This research was conducted in Minahasa Regency using a development (RD) method, namely developing a Sociology textbook Class X Semester 1 based on Minahasa local wisdom Maleo-leosan. Data were collected with a qualitative approach by conducting in-depth and structured interviews, observation, and documentation. The research results are the Minahasa community's local values in the form of local Maleo-leosan ideas. This can be elaborated in several sub-materials of sociology in Class X Semester 1, especially on the essential competencies of recognising and identifying the reality of individuals, groups, and social relations in society. Finally, of course, by developing to become a reference that teachers in schools can use as a reference book.